(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The article analyzes the factors shaping the competitiveness of the workforce in the context of an innovative economy, global labor market trends, the impact of digital transformation, automation and the platform economy on workforce competencies. Based on the experience of leading countries - the USA, the European Union, Japan, South Korea and Singapore, the organizational and economic mechanisms necessary for the formation of a competitive workforce in the labor market of Uzbekistan are substantiated. The results of the study indicate the importance of the quality of personnel training, digital skills, innovative forms of employment and investments in human capital.